KOEFISIEN PERPINDAHAN MASSA NATRIUM BENZOAT DENGAN AIR DALAM KOLOM ISIAN - Widodo, L.Urip (Jurnal Teknik Kimia, 2009)
Solid liquid mass transfer is important and wide application in many kind of chemical engineering process which followed by chemical reaction or non chemical reaction like solution, distillation and extraction processes. The research is to find the mass transfer coefficient between sodium benzoate with water on the fixed bed ( pipe circulation system) at the height of the bed as follows:3 cm; 4cm; 5cm; 7cm; 9cm and the flow rate as follows : 4.29cm  3/second; 5.3cm3 /second;6.16cm3/second; 7.62cm3/second; 9.05cm3 /second. With 3.2cm fix coulomb diameter and the particle diameter of 0.22mm sodium benzoate. Reside,the objective of this research was to find the mathematic model wich is influenced by the variable above used as general application especially for designing the equipment. By using the non lenear programe with all variables simultaneously found the equation model Key word: fixed bed; mass transfer coefficient; sodium benzoate;water.